Do students have sufficient knowledge of physics to take marine biology courses? - Sarkity Dios; Oprasmani Elfa; Irawan Bony; Sundari Putri Dwi (BIO Web of Conferences)
Physics and biology are two branches of science that have many connections. In marine biology courses, students must have a good basic concept of physics. The purpose of this study was to determine whether students’ physics knowledge is sufficient to follow marine biology lectures. This study is a quantitative descriptive study. The study was conducted in May 2024 in the Biology Education study program at Raja Ali Haji Maritime University involving 27 students in their third year of study. Data collection was carried out by testing and analyzing descriptively. The results of the study showed that students did not have sufficient knowledge of physics to be able to follow marine biology courses. This is indicated by the problems found by students in solving questions related to the Effect of the position of the earth, moon, and sun on sea tides, the relationship between salinity and density of seawater, the specific heat of seawater, and the impact of global warming on increasing temperature and rising sea levels. Therefore, action is needed to strengthen the basic concepts of physics of biology students so that when taking biology lectures related to physics, students will be able to understand them well.